Clinical Application of Soft Tissue Lasers in Periodontics - Narang, Sumit; Maytreyee, Rochira; Singh, Neha; Khare, Kshma; Jain, Prince (Journal of Orofacial Research, 2015)
Laser is an acronym for light amplification by stimulated emission of radiation. The use of laser in dentistry dates way back to 1960s. Since then, its use has increased manyfold. The dental lasers cut tissue by a principle known as photothermal interaction or photothermal ablation. Lasers are effectively used in operculectomies, gingival depigmentation, gingivectomies, and many more procedures. Laser cannot only be used for surgical procedures but can also be used as an adjunct to scaling and root planing. The diode laser is used on the soft tissue side of the periodontal pocket to remove the inflamed soft tissue and reduce the pathogens. Lasers have been suggested as an adjunct and/or alternative to conventional techniques for various periodontal procedures and considered superior with respect to easy ablation, decontamination, and hemostasis along with less operative and postoperative pain.